Comparative Analysis: Conceptualization of Teacher Quality in Indonesia and Singapore - Khairiyah, Ummu; Mariati, Pance; Suprapto, Nadi; Mariana, Neni (Indonesian Journal of Educational Research and Review, 2024)
Various countries have attempted to create standards of teacher competency that must be possessed with the ultimate goal of improving the quality of teachers and the education system in educational institutions. The purpose of this study is to analyze and compare the conception of teacher quality in the education systems of Indonesia and Singapore. The research method used in this study involves a literature review of articles and books that discuss the conception of teacher quality in Indonesia and Singapore. The steps in this research include topic identification, literature search, literature selection, literature evaluation, literature analysis, interpretation of analysis result, and article writing. The results of this this research indicate that Singapore is known to have one of the best education systems in the world, with a strong focus on teacher quality. Singapore has successfully developed high-quality teachers and provided strong support for the teaching profession. The teacher recruitment system in Singapore is highly selective and competitive, with high standars to ensure that prospective teachers have high competence. Meanwhile, Indonesia still faces challenges in improving the quality and welfare of teachers. However, there have been many efforts made to improve the education system and enhance teacher quality, namely through teacher quality improvement programs such as the Teacher Professional Education (Pendidikan Profesi Guru - PPG) and the Teacher Certification Program.